2005
DOI: 10.1002/jcp.20429
|View full text |Cite
|
Sign up to set email alerts
|

Loss of shear stress induces leukocyte‐mediated cytokine release and blood–brain barrier failure in dynamic in vitro blood–brain barrier model

Abstract: Brain ischemia is associated with an acute release of pro-inflammatory cytokines, notably TNF-alpha and IL-6 and failure of the blood-brain barrier. Shear stress, hypoxia-hypoglycemia, and blood leukocytes play a significant role in blood-brain barrier failure during transient or permanent ischemia. However, these mechanisms have not been studied as independent variables for in vitro ischemia. The present study, using a dynamic in vitro blood-brain barrier model, showed that flow cessation/reperfusion under no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
48
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(51 citation statements)
references
References 53 publications
3
48
0
Order By: Relevance
“…The reduction in forearm blood flow may lead to activation of tissue pro-inflammatory agents [25], and cachexia [26], thereby worsening outcomes. The consequences of such changes are exercise intolerance, early fatigue, and progression in heart failure [27,28].…”
Section: Discussionmentioning
confidence: 99%
“…The reduction in forearm blood flow may lead to activation of tissue pro-inflammatory agents [25], and cachexia [26], thereby worsening outcomes. The consequences of such changes are exercise intolerance, early fatigue, and progression in heart failure [27,28].…”
Section: Discussionmentioning
confidence: 99%
“…Compelling body of evidence has indicated that ischemia/reperfusion injury is closely associated with inflammatory reactions in vascular endothelium. For example, Krizanac-Bengez et al (2006) showed that exposure of a dynamic in vitro blood-brain barrier (BBB) model to flow cessation/ reperfusion resulted in an acute release of proinflammatory cytokines, such as tumor necrosis factor-α (TNF-α) and IL-6, and disruptions of BBB integrity. It was also found that myocardial ischemia/ reperfusion injury is related to an inflammatory response through attachment of polymorphonuclear leukocytes (PMNs) to the vascular endothelium with subsequent infiltration into the damaged myocardium (Hansen, 1995;Onai et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…These data were confirmed by measurements of IL-1b, IL-6, and MMP-9 release in medium samples (Figure 10). Pretreatment with ibuprofen significantly reduced the release of proinflammatory cytokines IL-1b, IL-6, and of MMP-9, all of which have been shown to be involved in the regulation of BBB permeability (Krizanac-Bengez et al, 2006;Shigemori et al, 2006). It should be noted that HCMEC/D3 cells grown in the DIV-BBB system under flow in the absence of astrocytes are capable of mimicking the physiological behavior of the BBB in vivo in response to systemic inflammation.…”
Section: Assessing the Role Of Inflammation In Bbb Failurementioning
confidence: 99%
“…In particular, the effect of loss of shear stress in presence of WBC under normoglycemic condition causes BBB failure by triggering proinflammatory events such as release of cytokines and MMPs and the activation of WBC (Gasche et al, 2006;Krizanac-Bengez et al, 2006;Latour et al, 2004). Figure 9A shows the baseline TEER values of the four separate control DIV-BBB modules established with the brain microvascular human cell line HCMEC/D3.…”
Section: Assessing the Role Of Inflammation In Bbb Failurementioning
confidence: 99%